Light-transmitting foam compositions and processes

JP2022549354A5Active Publication Date: 2025-02-26SEKISUI VOLTEC LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022519325
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2020-09-24
Publication Date
2025-02-26
Estimated Expiration
2040-09-24

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The polyolefin foam having improved light transmission has an average cell size of about 70 microns to about 500 microns, a total cell wall thickness / gauge ratio of about 0.15 to about 0.55, and a modulus of elasticity of about 0.00005 lb / in 2 ~Approx. 0.00050lb / in 2 The polyolefin foam has a basis weight of about 10% to about 50%, an L color solidity of about 95 to about 45, and a light transmittance of about 10% to about 50% in accordance with JIS K 7361-1. A process for producing a polyolefin foam with improved light transmittance includes extruding a foamable sheet at a pressure of about 1 psi to about 55 psi, and foaming the foamable sheet with a blowing agent having an average diameter of about 10 to about 25 microns to produce a foam having a light transmittance of about 10% to about 50% in accordance with JIS K 7361-1.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to methods and compositions for producing foams that are light transmissive, and more specifically to polyolefin foams that may be used to enable the transmission of light, including illuminated display information, through molded foam products such as those used in automotive, marine, aerospace, furniture, and other applications.

[0002] Priority claim This application claims the benefit of U.S. Provisional Patent Application No. 62 / 904,686, filed Sep. 24, 2019, the entirety of which is incorporated herein by reference. [Background technology]

[0003] Many applications require illuminated displays of information or symbols for a variety of purposes. For example, in automotive applications, display screens, gauges, icons, dashboard indicators, motion sensors, and other features are routinely illuminated to communicate with the driver and passengers about the vehicle's status and to facilitate interactive control of the vehicle and its systems through illumination of touch-sensitive display screens, including buttons, dials, and in-dash entertainment systems. Additionally, other areas of the vehicle are commonly illuminated with lights, such as bulbs, LEDs, or electroluminescent panels, for aesthetic and / or safety reasons, including ambient overhead and floor space lighting, cup holders, and interior trim features.

[0004] However, as digital touch-sensitive screens become more prevalent and available in vehicles, automotive designers are seeking creative and aesthetically pleasing options for providing lighting and lighting information without the use of screens, dials, and push buttons in the dash. Additionally, available surface space is limited in vehicles, and therefore lighting and control devices should operate optimally within that limit.

[0005] For example, US6464381B2 describes a vehicle interior component and lighting assembly, the interior component having a fabric disposed on a substrate or a foam layer, or both. An electroluminescent panel is disposed between the fabric and the substrate / foam layer, and can direct light from the panel through the foam and fabric. In this manner, the light source can be effectively hidden when not in use and can be incorporated into the interior component in a manner that requires little space. The vehicle interior component can include, for example, headliners, door panels, vehicle seats, rear decks, sun visors, and trunk panels. Furthermore, the arrangement can provide backlighting of touch switches and / or interior lighting via the switches. However, the disclosure is silent regarding the properties and type of foam that may be used.

[0006] US9963067B1 describes a luminescent interior trim structure for a vehicle, which includes an electroluminescent (EL) sheet capable of emitting light and disposed on the top side of a matrix, a foam layer disposed on the top surface of the EL sheet, and a skin layer disposed on the top surface of the foam layer. The foam is an injection molded thermoplastic elastomer and can be foamed chemically or physically. The patent teaches that the thickness of the foam can be determined according to the desired soft touch feeling of the foam, as well as the desired design and luminous area, in terms of the transmittance and scattering rate of the EL film light source, which depends on the size of the foam cells.

[0007] US2016 / 0280128A1 describes an automotive interior trim element including a translucent carrier component with a front and a back, a translucent covering material on the front of the carrier component, and a light source on the back of the carrier component, where the translucent covering material has a Shore A hardness in the range of 60-80, the interior trim element includes at least one surface of a storage tray or compartment of the vehicle that is visible to an occupant of the vehicle, and the light source illuminates the visible surface of the storage tray or compartment. The patent further describes that the translucent covering material can be laminated with a translucent backing material such as a polyolefin foam, and that the various materials of the translucent covering material and, if applicable, the backing layer, and the translucent carrier must be carefully matched to one another to achieve suitable light transmission and uniform distribution across the surface of the interior trim element, including that the materials should also preferably be UV and heat resistant.

[0008] However, none of these disclosures provide guidance on how to achieve many of the desired physical properties of automotive foams while maximizing or controlling light transmission to sufficient levels. For example, foams are still Thickness They must meet various industry specifications relating to density, compression deflection, gel content, tensile strength, elongation, tear strength, thermal stability, modulus, color, and many other properties as per the requirements of specific applications.

[0009] Thus, there is an unmet need in the market for an optimized foam that allows for maximum and controlled levels of light transmission while at the same time meeting the many physical specifications required by the industry. Ideally, such a foam would maximize light transmission while at least maintaining the physical specifications desired by the industry. Summary of the Invention

[0010] This Summary is provided to introduce a selection of concepts that are further described below in the Detailed Description. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.

[0011] The present disclosure relates to optically transparent foam compositions and related processes.

[0012] In one embodiment, the polyolefin foam with improved light transmission has an average cell size of about 70 microns to about 500 microns and a total cell wall thickness / molecular weight of about 0.15 to about 0.55. Sheet Thickness Ratio is approximately 0.00005 lb / in 2 ~about 0.00050lb / in 2 The paper has one or more specifications including a basis weight of about 95 to about 45, an L color solid value of about 95 to about 45, and a light transmittance of about 10% to about 50% in accordance with JIS K7361-1.

[0013] In another embodiment, a process for producing a polyolefin foam having improved light transmission includes extruding a foamable sheet at a pressure of about 1 to about 55 psi and foaming the foamable sheet with a blowing agent having an average diameter of about 10 to about 25 microns to produce a foam having a light transmission of about 10% to about 50% in accordance with JIS K7361-1. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 shows % light transmission versus foam basis weight. [Diagram 2] FIG. 1 shows % light transmission versus foam basis weight and color. [Figure 3A] FIG. 1 shows % light transmission versus L color stereoscopic value of foams. [Figure 3B] FIG. 1 shows the % light transmittance versus a-color steric value of the foam. [Figure 3C] FIG. 1 shows % light transmission versus b-color stereoscopic value of foams. [Figure 4A]1 is a graph showing the percentage of light transmittance versus foam cell size. [Figure 4B] 1 is a graph showing foam cell size versus foam extrusion air pressure. [Figure 4C] 1 is a graph showing % light transmission versus foam extrusion air pressure. [Figure 5A] 1 is a graph showing % light transmission versus total wall thickness / sheet thickness ratio of foam. [Figure 5B] 1 is a graph showing foam extrusion air pressure versus total wall thickness / sheet thickness ratio. [Figure 6] 1 is a graph showing foam extrusion air pressure versus L, a, b scale foam color. [Figure 7A] 1 is a graph showing foam cell size versus blowing agent particle size. [Figure 7B] 1 is a graph showing the ratio of total wall thickness / sheet thickness to the foaming agent particle size. [Figure 7C] 1 is a graph showing the % light transmittance versus foaming agent particle size. [Figure 8A] 1 is a graph showing cell size of polypropylene trial foam samples. [Figure 8B] 1 is a graph showing wall thickness to sheet thickness ratios for polypropylene trial foam samples. [Figure 8C] 1 is a graph showing the % Light Transmission of polypropylene trial foam samples. [Figure 9] 1 is a graph showing % light transmission versus basis weight for polypropylene trial foam samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Disclosed herein are polyolefin foam compositions and methods for making the same, said foams with improved light transmission properties suitable for a wide variety of applications requiring the transmission of light through the foam, including, for example, illuminated indicators and ambient lighting for vehicle interior trim. Foams of the present disclosure may be considered "light-transmitting" if at least a portion of incident visible light is transmitted through the foam and can be readily detected, such as, for example, semi-transparent and translucent foams.

[0016] Suitable polymers or resins for use in the foamable sheet include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ethylene vinyl acetate (EVA), polypropylene (PP), ethylene propylene diene monomer (EPDM), thermoplastic olefin (TPO), thermoplastic elastomer (TPE), and rubber. Individual resins may be selected for light-transmitting foams, as well as blends of two or more resins. Suitable foaming agents may include, for example, azodicarbonamide (ADCA).

[0017] In one embodiment, polyolefin foams having improved light transmission can be produced having an average cell size of about 70 microns to about 500 microns, preferably about 80 microns to about 465 microns, and more preferably about 195 microns to about 465 microns, as well as any combination of the aforementioned upper and lower limits of these ranges.

[0018] In another embodiment, the polyolefin foam having improved light transmission has a total cell wall thickness / viscosity of about 0.15 to about 0.55, preferably about 0.18 to about 0.50, and more preferably about 0.22 to about 0.50, as well as any combination of the aforementioned upper and lower limits of these ranges. Sheet Thickness The ratio can be made to have:

[0019] In another embodiment, the polyolefin foam has an improved light transmission of about 0.00005 lb / in 2 ~about 0.00050lb / in2 , more preferably about 0.00008 lb / in 2 ~Approx. 0.00043lb / in 2 and most preferably about 0.00008 lb / in 2 ~Approx. 0.00027lb / in 2 The sheet can be manufactured to have a basis weight of

[0020] In another embodiment, polyolefin foams with improved light transmission can be produced with an L color stereo value of from about 95 to about 45, or from about 91 to about 65, but most preferably as close to 100 as possible.

[0021] In another embodiment, polyolefin foams having improved light transmission can be produced having a light transmission of about 10% to about 50%, about 15% to about 45%, about 15% to about 35%, about 20% to about 40%, or about 25% to about 35%, or any combination of the aforementioned upper and lower limits of these ranges, but most preferably as high as possible.

[0022] In another aspect, a process for producing a polyolefin foam having improved light transmission comprises extruding a foamable sheet at a pressure of from about 1 to about 55 psi, preferably from about 2 to about 30 psi, and more preferably from about 25 to about 30 psi, or alternatively at atmospheric pressure, to produce a foam having a light transmission of from about 10% to about 50%, from about 15% to about 45%, from about 15% to about 35%, from about 20% to about 40%, or from about 25% to about 35, or any combination of the aforementioned upper and lower limits of these ranges, but most preferably as high as possible.

[0023] In another embodiment, a process for producing a polyolefin foam having improved light transmission comprises foaming a foamable sheet with a blowing agent having an average particle size of about 10 to about 25 microns, more preferably about 12 to about 20 microns, to produce a foam having an average particle size of about 10% to about 50%, about 15% to about 45%, about 15% to about 35%, about 20% to about 40%, about 25% to about 35%, or any combination of the aforementioned upper and lower limits of these ranges, but most preferably as high as possible.

[0024] Experimental Method A Konica Minolta Benchtop Spectrophotometer CM-3600A was used to measure the light transmittance of various foam samples prepared according to the following description, according to the Japanese Industrial Standard JISK7361-1 (Measurement of Total Light Transmittance of Transparent Materials). JISK7361-1 is based on ISO13468-1. A Hunter Lab color spectrophotometer was used to measure the color of the foam according to the standard CIELAB color space (also known as the CIE L*a*b* color space) defined by the International Commission on Illumination.

[0025] The formulations in Table 1A below were used to prepare foam samples used in the experiments described further below. [Table 1A]

[0026] where LLDPE is linear low density polyethylene, h-PP is homopolymer polypropylene, TPO is thermoplastic polyolefin, TPE is thermoplastic elastomer, AO is antioxidant, and further, a blowing agent (FA) such as azodicarbonamide was used in an amount (AR) as needed to achieve the desired foam density as will be understood by one skilled in the art and tested in the examples below. Cream color as opposed to white was achieved by selecting a heat stabilizer that affects the base color of the foam.

[0027] The foam formulations for each test sample were blended and extruded through a single or twin screw extruder and sheet die at a temperature above the melt temperature of the polymer and below the activation temperature of the blowing agent to produce a foamable sheet. Extrusion was carried out under vacuum or below atmospheric pressure (atm) for all samples unless otherwise noted, such as those indicated by "open air" extrusion at atmospheric pressure, or those indicated in the examples below at psi above atmospheric pressure. Suitable air pressures for extrusion below 1 atm can be, for example, from about 1 to about 14 psi (where 1 atm = 14.7 psi).

[0028] The extruded sheet was physically irradiated with an electron beam to physically crosslink the foam at the desired gel content, preferably about 30% to about 65%, and then the sheet was foamed in a foaming oven at or above the activation temperature of the foaming agent to obtain a foamed sample for testing.

[0029] The physical and performance properties of the foam samples produced were measured according to industry standard specifications commonly used for, for example, automotive interior foams, and the results are shown below in Table 1B, along with the MD measured in the machine direction of the foam extrusion and the CM measured in the cross direction of the foam extrusion. As one of ordinary skill in the art would understand, stretch ratio refers to the foam's properties with respect to thermoforming, and orange peel refers to surface degradation during thermoforming. [Table 1B-1] [Table 1B-2]

[0030] As shown in Table 1B, the foam samples exhibit performance specifications suitable for, for example, automotive interior trim molded foam components.

[0031] Example 1 - % Light Transmission vs. Foam Basis Weight Foam samples, listed in Table 2 below, were produced according to the formulations in Table 1A to have different basis weights and each was tested for % light transmission according to JIS K7361-1 as previously described. [Table 2]

[0032] As shown by the results in Table 2 and the corresponding graph in FIG. 1, color affects light transmission, with the white sample exhibiting better light transmission than the cream sample using the same polypropylene (PP) resin. Furthermore, the lower the basis weight of the foam sample, the better the light transmission properties observed. The white PE sample also showed the same trend with respect to basis weight, proving that PE performs similarly to PP. Although a maximum light transmission of 34% is shown in Table 2, it can be understood that foams having higher light transmission values, including from about 35% to about 50%, can be achieved using various techniques, alone or in combination, as taught in this disclosure, including the following. For example, the white PP sample 1 in Table 2 can be extruded at a higher air pressure to adjust for a higher light transmission. Additionally, the basis weight of the foam can be gradually lowered to increase the light transmission, for example, to about 0.00005 lb / in 2 It can be lowered to.

[0033] Example 2 - % Light Transmission vs. Foam Color and Extrusion Conditions Different colored foam samples, listed in Tables 3 and 4 below, were prepared by adding colorants to the white PE formulation of Table 1A (<1 atm) and then tested for overall light transmission at various basis weights, which included measuring the L, a, and b color solid values ​​using the Hunter Lab color spectrophotometer previously described, with the "L" value on each scale indicating the level of lightness or darkness, the "a" value indicating redness or greenness, and the "b" value indicating yellowness or blueness. All samples except the open air green were extruded (<1 atm). [Table 3] [Table 4]

[0034] As shown by the results in Table 3 and the corresponding graph in Figure 2, a comparison of the colored foams (<1 atm) to the open air green showed that extrusion at atmospheric pressure compared to below atmospheric pressure resulted in a higher % light transmission. Additionally, natural, white, and yellow were all found to have higher % transmission compared to the other colors. Thus, making open air extruded foams in natural, white, or yellow results in a significant improvement in % transmission.

[0035] As shown by the results in Table 4 and the corresponding graphs in Figures 3A, 3B, and 3C, the measured "L" values ​​of the foams had a direct relationship to the % Light Transmission across the basis weight, with higher L values ​​resulting in higher % Transmission (Figure 3A), while there was no direct relationship to the % Light Transmission observable between the "a" values ​​(Figure 3B) and "b" values ​​(Figure 3C) across the basis weight, indicating that the relative redness versus greenness or yellowness versus blueness of the foam did not affect the % Light Transmission. Thus, it can be appreciated that adjustment of the "L" value of the produced foams, in combination with other factors including, but not limited to, foam color and extrusion air pressure, can also be used to increase or decrease the % Light Transmission as needed, including achieving % Light Transmission ranges beyond those explicitly set forth in Tables 3 and 4.

[0036] Example 3 - % Light Transmission vs. Extrusion Air Pressure and Cell Size The foam samples listed in Table 5 below were measured for % light transmission upon extrusion at various air pressures and basis weights to produce foam samples of various cell sizes. The cream PP2 formulation was subjected to increasing extrusion air pressures as listed in Table 5 below. [Table 5]

[0037] As shown by the results in Table 5 and the corresponding graphs in Figures 4A, 4B, and 4C, the light transmission improved as the size of the cells increased because there was less material, such as cell walls, blocking the path of light (see, e.g., Figure 4A). As shown in the graph in Figure 4B, the cell size increased as more air pressure was applied to the foam extrusion process, but after about 10-20 psi, the cell size was adversely affected. As shown in the graph in Figure 4C, the % light transmission increased with increasing pressure (psi), which also corresponds to cell size, until about 10-20 psi, where the cell size was adversely affected along with the % light transmission. Thus, it can be seen that the % light transmission of the foam can be tuned by controlling the cell size as another factor alone or in combination with additional techniques taught by the present disclosure, including achieving % light transmission ranges beyond those explicitly set forth in Table 5.

[0038] Example 4 - % Light Transmission vs. Cell Wall Thickness The foam samples listed in Table 6 below were measured for % light transmission based on extrusion at various air pressures and basis weights to produce foam samples of various cell wall thicknesses. Cream PP2 formulation was subjected to increasing extrusion air pressures as listed in Table 6 below. The total wall thickness was calculated as the average number of cell walls multiplied by the average individual wall thickness (measured in microns) from the first surface to the second surface of the foam (i.e., through the thickness of the foam as light is transmitted). The total wall thickness was calculated as the average number of cell walls multiplied by the average individual wall thickness (measured in microns) from the first surface to the second surface of the foam (i.e., through the thickness of the foam as light is transmitted). Sheet Thickness By dividing by the total wall thickness / Sheet Thickness The ratio was calculated. [Table 6]

[0039] As shown in the results in Table 6 and the corresponding graphs in Figures 5A and 5B, the total wall thickness / Sheet Thickness As the ratio decreases, the % light transmission increases because there is less material obstructing the path of light (see, for example, FIG. 5A). As shown in FIG. 5B, the foam ThicknessThe distance of material that light had to travel through decreased as the extrusion air pressure increased. As shown in Figure 4C, and as previously mentioned, the % light transmittance increased with increasing pressure (psi), which corresponds to cell size, and the cell wall thickness increased with increasing pressure (psi), up to about 10-20 psi, where cell size along with % light transmittance was negatively affected by the foam. Thickness Therefore, the % light transmittance of the foam is calculated as the total wall thickness of the foam divided by Sheet Thickness It will be appreciated that the ratio can be adjusted by controlling another factor alone or in combination with additional techniques taught by this disclosure, including achieving % light transmission ranges beyond those explicitly set forth in Table 6.

[0040] Example 5 - Effect of extrusion air pressure on foam color The foam samples listed in Table 7 below, foamed at different extrusion air pressures, were measured using a Hunter Lab color spectrophotometer to measure the L, a, and b color solid values ​​as described above. [Table 7]

[0041] As shown by the results in Table 7 and the corresponding graph in Figure 6, increasing the extrusion air pressure decreased the "L" value, i.e., the foam became darker while the "a" and "b" values ​​were not affected.

[0042] Example 6 - % Light Transmission vs. Blowing Agent Diameter The foam samples listed in Table 8 below were measured for % light transmission based on producing foam samples using blowing agents (FA) with different average particle sizes in the cream PP2 formulation. [Table 8]

[0043] As shown by the results in Table 8 and the corresponding graphs in Figures 7A, 7B, and 7C, a larger average foam diameter results in a larger cell size (Figure 7A), and a larger foam diameter results in a thinner wall thickness (Figure 7B), which in turn results in an improved % Light Transmission with increasing foam diameter (Figure 7C). Thus, it can be seen that the % Light Transmission of a foam can be tuned by controlling the foam diameter as another factor alone or in combination with additional techniques taught by the present disclosure, including achieving % Light Transmission ranges beyond those explicitly set forth in Table 8.

[0044] Example 7 - Trial Results 1 To target improved % light transmission for the automotive interior trim market, foam samples were further optimized according to the formulation for PP trials in Table 1A. [Table 9]

[0045] As shown by the results in Table 9 and the corresponding graphs in Figures 8A, 8B, and 8C, foam color did not affect cell size, but the open air sample produced much larger cells (Figure 8A), and foam color did not affect cell wall thickness either, but the open air sample produced thinner cell walls than the standard sample extruded at subatmospheric pressure (Figure 8B). As the trial results show, utilizing the techniques taught by the present disclosure, the % light transmission of a standard grade foam cream PP compatible with the automotive market could be increased incrementally from 12% to 33%, which was not considered the largest increase since other techniques could be utilized to further increase the % light transmission value to about 50%, etc. With reference to Figure 8C, cream PP vs. white PP resulted in a 7% light transmission, and white PP to open air white PP1 resulted in an additional 10% increase in light transmission, resulting in an overall 17% or about 2.5 times increase in light transmission compared to the cream PP sample.

[0046] Example 8 - Trial Results 2 To target improved % light transmission for the automotive market, foam samples were further optimized according to the formulation for PP testing in Table 1A and then compared to cream PP and white PP samples across basis weights. [Table 10]

[0047] As shown by the results in Table 10 and the corresponding graph in Figure 9, the open air white PP outperformed all other PP samples at each corresponding basis weight.

[0048] In accordance with the present disclosure, the light transmission of a foam is determined by the cell size, cell wall thickness, total cell wall thickness / Sheet Thickness Through proper selection and control of various parameters including ratio, color (including L value), and basis weight, the foam may be improved and / or controlled and tailored to desired ranges suitable for a wide variety of illuminated end uses. The present disclosure is the first to enable the production of such foams through the teaching of suitable methods including, as non-limiting examples, proper selection of blowing agent diameter, extrusion air pressure, and compatible formulations.

[0049] Although the invention has been described with reference to exemplary embodiments, those skilled in the art will recognize that various modifications may be made and equivalents substituted for elements thereof without departing from the scope of the invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the invention without departing from its essential scope. Therefore, it is not intended that the invention be limited to the particular embodiments disclosed, but the invention is intended to include all embodiments falling within the scope of the appended claims.

Claims

1. A polyolefin foam sheet, comprising: an average cell size between 70 microns and 500 microns; A total cell wall thickness / sheet thickness ratio of 0.15 to 0.55; 0.00005lb / in 2 ~0.00050lb / in 2 and an L color stereo value of 95 to 45; A polyolefin foam sheet having a light transmittance of 10% to 50% conforming to JIS K7361-1.

2. 2. The polyolefin foam sheet of claim 1, wherein the average cell size is from 80 microns to 465 microns.

3. 2. The polyolefin foam sheet of claim 1, wherein the average cell size is from 195 microns to 465 microns.

4. The basis weight is 0.00008 lb / in 2 ~0.00043lb / in 2 The polyolefin foam sheet according to claim 1 ,

5. The basis weight is 0.00008 lb / in 2 ~0.00027lb / in 2 The polyolefin foam sheet according to claim 1 ,

6. The polyolefin foam sheet according to claim 1, wherein the L color stereoscopic value is 91 to 65.

7. The polyolefin foam sheet according to claim 1, wherein the light transmittance is 15% to 45%.

8. The polyolefin foam sheet according to claim 1, wherein the light transmittance is 15% to 35%.

9. 2. The polyolefin foam sheet according to claim 1, wherein the total cell wall thickness / sheet thickness ratio is 0.18 to 0.

50.

10. 2. The polyolefin foam sheet according to claim 1, wherein the total cell wall thickness / sheet thickness ratio is 0.22 to 0.

50.

11. The polyolefin foam sheet of claim 1, wherein the polyolefin foam sheet is made from one or more resins selected from the group consisting of low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ethylene vinyl acetate (EVA), polypropylene (PP), ethylene propylene diene monomer (EPDM), thermoplastic olefin (TPO), thermoplastic elastomer (TPE), and rubber.

12. 1. A process for producing a polyolefin foam comprising: extruding the foam sheet with an air pressure of 1 psi to 55 psi; and foaming the foamable sheet with a foaming agent having an average diameter of 10 to 25 microns to produce a foam having a light transmittance of 10% to 50% in accordance with JIS K7361-1.

13. The process of claim 12, further comprising extruding the foamable sheet with an air pressure of between 2 psi and 30 psi.

14. The process of claim 12, further comprising extruding the foamable sheet with an air pressure of 25 psi to 30 psi.

15. 13. The process of claim 12, further comprising extruding the expandable sheet at atmospheric pressure.

16. The process of claim 12, further comprising foaming the foamable sheet with a foaming agent having an average diameter of 12 microns to 20 microns.

17. 13. The process of claim 12, wherein the blowing agent comprises azodicarbonamide (ADCA).

18. 13. The process of claim 12, further comprising crosslinking the foamable sheet prior to foaming the foamable sheet.

19. The process of claim 12, wherein the light transmittance is between 15% and 45%.

20. The process of claim 12, wherein the light transmittance is between 15% and 35%.